Oxandra unibracteata (Annonaceae), a new species from the Atlantic Forest and a new synonym of O. nitida - Lopes, Jenifer De Carvalho; Junikka, Leo; Mello-Silva, Renato (Phytotaxa, 2013)
A new species of Oxandra from the Brazilian Atlantic Forest is described and illustrated, and a key to the species of Oxandra from the Brazilian Atlantic Forest is presented. Oxandra unibracteata is the only species within the genus with a single bract on the pedicel. It resembles O. reticulata; they share reticulate leaves but can be distinguished by leaf shape and length of the pedicel. Oxandra opaca is proposed as a new synonym of O. nitida.